Venoarterial extracorporeal membrane oxygenation decannulation using the novel Manta vascular closure device. Issue 4 (1st June 2020) - Bemtgen, Xavier; Heidt, Timo; Zotzmann, Viviane; Rilinger, Jonathan; Wengenmayer, Tobias; Biever, Paul M; von zur Mühlen, Constantin; Benk, Christoph; Bode, Christoph; Staudacher, Dawid L
Abstract : Aims: Removal of large calibre arterial sheaths, as employed in venoarterial extracorporeal membrane oxygenation, is still associated with a high risk for vascular access site complications. In this study, we investigated the large bore Manta closure device as an option for venoarterial extracorporeal membrane oxygenation decannulation. Methods and results: Sixteen patients weaned from venoarterial extracorporeal membrane oxygenation between January–June 2019 were prospectively included in a registry (eight during extracorporeal cardiopulmonary resuscitation, seven with severe cardiogenic shock and one patient with fulminant pulmonary embolism). All patients had an arterial sheath removed at bedside using the Manta device achieving rapid haemostasis without clinically relevant complications afterwards. A computed tomography angiography was available for 11 patients (68.8%) and reassessed with regards to relevant pathologies at the closure device. Average intraluminal area was 40.4 mm 2 (12.2–76.3 mm 2 ) at the closure site. All devices but one were correctly deployed. Three patients (27.3%) had a visible thrombus at the closure device resulting in a >60% stenosis, two of which had a puncture site distal of the femoral artery bifurcation. Conclusion: Decannulation from venoarterial extracorporeal membrane oxygenation using the Manta closure device is a viable approach for rapid haemostasis, but is also associated with a significant risk of thrombotic vessel stenosis. These preliminary findings indicate that puncture in near proximity or distal to the femoral bifurcation might identify patients at risk and further studies are needed.